THE INFLUENCE OF FINANCIAL PERFORMANCE, COMPANY SIZE, AND GOOD CORPORATE GOVERNANCE ON FINANCIAL DISTRESS - Rohman, Zanuar Lutfi; Arofah, Triani; Herwiyanti, Eliada; Wulandari, Ratu Ayu Sri (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
This study aims to determine and analyze the effect of financial performance, company size, and good corporate governance on financial distress in raw goods sector companies listed on the Indonesia Stock Exchange for the period 2020 - 2023. The independent variables studied are: (1) Profitability proxied by Return on Assets (ROA); (2) Liquidity proxied by Current Ratio (CR); (3) Leverage proxied by Debt to Equity Ratio (DER); (4) Company size proxied by Natural Logarithm of Total Assets; (5) Managerial Ownership; (6) Institutional Ownership; (7) Independent Board of Commissioners; and (8) Audit Committee. The dependent variable is Financial Distress with the Modified Altman Z-Score indicator. This study uses three theories as the basis of its research, namely agency theory, signal theory, and pecking order theory. This research is a causal quantitative research. The sampling technique used is purposive sampling. The data analysis used is logistic regression test by utilizing Statistical Package for Social Science (SPSS) v25 software. The results showed that the profitability variable had a significant negative effect on financial distress and the liquidity variable had a significant positive effect on financial distress. Meanwhile, the variables of leverage, company size, and managerial ownership, institutional ownership, independent board of commissioners, and audit committee have no effect on financial distress. The implications of this research are expected to contribute to expanding the literature on the effect of financial performance, company size, and good corporate governance (GCG) on financial distress. The limitations of this study are the sample coverage which only focuses on the raw goods sector, research variables, variable proxies (measuring instruments), and observation period. Further research is recommended to use a wider sample coverage to obtain more comprehensive results.